2016
DOI: 10.1515/intag-2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

Calorific evaluation and energy potential of grape pomace

Abstract: A b s t r a c t. This article deals with energetic evaluation and potential of pomace -a waste product originating during production of grape wine. Calorimetric analysis of 19 grapevine varieties was performed in 2013 and 2014. The aim was to specify their combustible limit and the gross calorific value. The evaluations were performed on pristine pomace, pomace without seeds, and only on seeds themselves. The results obtained imply that pomace is an interesting energetic resource with a gross calorific value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The sample of white grape pomace in the dry state contained 6.03 wt.% hydrogen. Similar contents in white grape pomace were measured by Burg et al [ 51 ] at 5.82 wt.%. At higher torrefaction temperatures, hydrogen content decreased to 5.57 wt.% in the GP-W sample at 275 °C.…”
Section: Resultssupporting
confidence: 87%
“…The sample of white grape pomace in the dry state contained 6.03 wt.% hydrogen. Similar contents in white grape pomace were measured by Burg et al [ 51 ] at 5.82 wt.%. At higher torrefaction temperatures, hydrogen content decreased to 5.57 wt.% in the GP-W sample at 275 °C.…”
Section: Resultssupporting
confidence: 87%
“…Renewable energy sources play a key role in current global strategies to reduce greenhouse gas emissions and, partly, in efforts to replace fossil fuels [1,2]. Biomass is one of the most important sources of renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of grape pomace within combustion technologies seems to be favourable in particular in power sector dominated so far by coal-fired units (like in Poland) by fostering positive financial feedback (existing boilers may be easily adopted). It has been previously reported that this type of grape marc utilisation within power sector is financially reasonable and technically justified in both small and large wineries [6,19]. Moreover, in this case it may be easier to introduce wine pomace in power sector through one general technical solution.…”
Section: A C Bmentioning
confidence: 99%
“…nocondensing boilers. According to [19], to reduce a moisture content of grape pomace from 60% to 8%, approximately 1.5 GJ of heat need to be utilised. However, that value may be covered by renewable energy streams (solar, geothermal) or waste heat (from fumes) in integrated driers.…”
Section: Physicochemical Analysis Of Grape Pomacementioning
confidence: 99%